Establishing a New Neurointerventional Facility in a Remote Area of a Low–Middle Income Country (LMIC): Initial Experience - Yadav, Nishtha; Kumar, Ambuj; Hedaoo, Ketan; Jain, Anivesh; Singh, Kamalraj; Vikram, Aditya (Asian Journal of Neurosurgery, 2022)
Background Timely performed Neurointervention procedures in patients with neurovascular disorders save them from mortality and lifelong morbidity, in addition to relieving the immense economic and social burden associated with these diseases.Materials and Methods We retrospectively reviewed data of neurointerventions performed in our hospital from November 2019 till March 2021. Patient age, sex, diagnosis, preoperative, and postoperative imaging findings were collected and analyzed. Types of procedures, success/failure, procedure-related and procedure-unrelated complications were noted and described.Results Total 161 procedures were done (diagnostic n = 89, therapeutic n = 72). Among the 72 cases of therapeutic procedures, angiographic success was noted in 60 cases, partial success was noted in 5 cases (RR grade 3 occlusion) and failure was noted in 7 cases [mechanical thrombectomy (n = 2), coiling (n = 1), flow diverter (n = 1), Caroticocavernous fistula (n = 1), cerebral Arteriovenous malformation (n = 2)]. Among therapeutic cases (n = 72), patient outcome was categorized as improved (with mRS 0-2 at discharge) in 64 cases (60 neurointerventions, 4 converted to surgery), morbidity in form of weakness was noted in 2 cases, mortality was noted in 8 cases. There were no hemorrhagic complications due to rupture or dissection. Ischemic complications were noted in form of thromboembolic complications in three cases and vessel occlusion (delayed MCA occlusion) in one case.Conclusion With recent efforts by medical associations and governments to provide access to these lifesaving, disability averting neuro-interventions, it’s important to recognize and define challenges in implementation of neuro-intervention services. In this article, we share our early experience in establishing a neurointervention facility in a backward region of a low–middle income country.
Keywords: neurointervention; LMIC; endovascular